Organics-based aqueous batteries: Concept for stationary energy storage with resource feasibility - Xinyue Zhang; Tian Bao; Hong-bin Sun (Resources Chemicals and Materials)
The integration of large-scale energy storage batteries and sustainable power generation is a promising way to reduce the consumption of fossil fuels and lower CO2 emissions. The significant materials demand for large-scale energy storage will address the limitation of resource availability. Organics-based aqueous batteries employing organic materials emerge as a promising settlement to face this challenge. Such types of batteries satisfy requirements related to elemental availability, inherent safety, cost affordability, technical reliability, and environmental sustainability meeting the demands of large-scale, long-duration energy storage.